Aortic annulus to left coronary distance as a predictor for persistent left bundle branch block after TAVI. Issue 4 (1st April 2016) - Hein‐Rothweiler, Ralph; Jochheim, David; Rizas, Konstantinos; Egger, Alexander; Theiss, Hans; Bauer, Axel; Massberg, Steffen; Mehilli, Julinda
Abstract : Objectives: To identify potential predictors for ventricular conduction delay and to evaluate the impact of interventricular dyssynchrony on mortality after implantation of a balloon‐expandable aortic valve (BEV). Methods and results: Clinical, computertomographical (CT), and electrocardiographical (ECG) data from 225 transcatheter aortic valve implantation (TAVI) patients were analyzed. Procedures were performed between May 2010 and September 2013 via transfemoral access using a BEV. Incidence of new‐onset left bundle branch block (NOP‐LBBB) at discharge was 23.1% (n = 52). Predictive factors for NOP‐LBBB were first degree atrioventricular (AV) block (odds ratio (OR): 3.91, 95% confidence interval (CI): 1.58 to 9.64), area cover index (OR: 1.83, 95% CI: 1.26 to 2.67), annulus calcification > first degree (OR: 3.01, 95% CI: 1.36 to 6.66), and annulus to left coronary distance (OR: 0.65, 95% CI: 0.44 to 0.96). At 1‐year follow‐up, no significant difference was observed concerning all‐cause mortality (15.6% among non NOP‐LBBB and 9.6% among NOP‐LBBB patients, P = 0.278) and cardiovascular mortality (4.6% among non NOP‐LBBB and 5.8% among NOP‐LBBB patients, P = 0.737). Conclusion: In addition to previous predictors, annulus to left coronary distance and area cover index have been identified as new predictors for NOP‐LBBB. NOP‐LBBB showed no relevant impact on mortality after one year. Further investigation including larger populations and longer follow‐up is required to confirm these findings and develop an algorithm for identification of patients at risk for NOP‐LBBB associated adverse events. © 2016 Wiley Periodicals, Inc.